The shari ‘ah option and the attitude of yoruba muslims towards multiple legal system in Nigeria (2017)
The paper addresses the operation of multiple legal systems in a multiethnic and multi-religious environment of which Nigeria is part. The issue of multiple legal systems has been a subject of deliberations by jurists and anthropologists. Nevertheless, despite the volume of literature on multiple legal systems, none has elicited the opinion of Yoruba Muslims on their opinion of maintaining the legal system in Nigeria with particular reference to Yorubaland. The paper elicited the views of Yoruba Muslims on their acceptability or otherwise of a multiple legal system where the Shari‘ah Law will be implemented on Muslims within the Yoruba domain in Nigeria. Several futile attempts at institutionalising Shari‘ah law, especially with regard to personal law have been made in some parts of Yorubaland in Nigeria. Overwhelming majority of the respondents did support a multiple legal system with the Shari’ah Law as a component. However, the awareness of conflict resolution panels in line with Islamic teachings is low. There is therefore the need to step up publicity in that regard.